Did BUMDes’s Resources Contribute to Village Economic Development? - Ni Kadek Sinarwati Sinarwati; I Nengah Suarmanayasa (International Journal of Social Science and Business, 2023)
The presence of Village-Owned Enterprises (BUMDes) with available resources such as capital, profits and employees are expected to be a driving force for village economic development to reduce rural poverty. Various programs have been implemented to increase BUMDes resources, but research on the contribution of BUMDes resources to village economic development is still limited. The purpose of this study is to analyze the contribution of BUMDes resources to village economic development. This study used a causal quantitative approach, using multiple linear regression analysis as a data analysis method. The population of this study consisted of BUMDes located in 116 villages in Bali Province. The research sample was selected using random sampling technique, with a total sample of 116 BUMDes that had reported data on the amount of capital, the number of business results, and the number of workers. The results showed that the percentage of capital and employees contributed to the economic development of the village, while the percentage of profits did not. The implication of this finding is that both central and local governments, including village governments, provide capital support for BUMDes business development. The government at the district level through the Village Community Empowerment Office is expected to provide ongoing assistance to improve the competence of human resources in BUMDes. Researchers are further advised to use more than one year of data and analyze other BUMDes resources such as technology, employee expertise, age of BUMDes and government assistance to BUMDes.